Jewish problem in the Polish Communist Party = Problem żydowski w Komunistycznej Partii Polski - Cimek, Henryk (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Jews accounted for approx. 8-10% of the population of the Second Republic and in the communist movement (Polish Communist Party and Polish Communist Youth Union) the rate was approx, 30%, while in subsequent years it much fluctuated. The percentage of Jews was the highest in the authorities of the party and in the KZMP. This had a negative impact on the position of the KPP on many issues, especially in its relation to the Second Republic.
Keywords: Jews; the Communist Party of Poland; separatism; The Second Republic of Poland; Żydzi; Komunistyczna Partia Polski; separatyzm; II (druga) Rzeczpospolita